Analisis Sistem Pengendalian Internal Penggajian Karyawan: Studi Kasus Pada Pt. Delta Laras Wisata Cabang Sukabumi - mahardhita, audya; Ade Sudarma (AKUNTANSI 45, 2024)
This study aims to explain the internal control system at PT. Delta Laras Wisata Sukabumi Branch and the system applied in the employee payroll process. This study uses a descriptive qualitative method with a case study approach, data obtained from observations, interviews, observations and documentation. The results of the study at PT Delta Laras Wisata, Sukabumi Branch, the payroll system that has been implemented has been running well and is effective. Documents, accounting records, and payroll procedures have been carried out according to existing theory. However, there are only a few that are not appropriate, such as in the documents, there is no salary envelope, because the company has made salary payments by transferring to each account. Then in the time recording procedure there are still employees who arrive late and don't do their fingerprints and at PT. Delta Laras Wisata, Sukabumi branch, the control system is running well and effectively. All procedures are in accordance with existing theories such as organizational systems, authority systems and recording procedures, healthy practices and competent employees.